Latent Medical Conditions of Drivers Involved in Road Traffic Collisions in Ghana: Implication from Autopsy Findings - Paul Poku Sampene Ossei; Eric Agyeman-Duah; William Gilbert Ayibor; Nicholas Niako; Kwakye Foster Safo (SAGE Publishing, 2021)
Background: Unlike some neighboring countries like Nigeria, few studies on actual causes, impact and the prevention of road traffic collisions have been carried out in Ghana. There is the need for further research and this study sought to link injuries that caused the death of drivers involved in vehicular collisions to the latent possible contributing diseases and medical conditions in these drivers and how these conditions predispose them to the collisions. Methods: This is a retrospective study that used the forensic autopsy records of driver fatalities and various injuries and medical conditions of drivers involved in road traffic collisions. Information on all drivers was retrieved from archives at the Komfo Anokye Teaching Hospital' Pathology Unit. Demographics and cause of death were used in selecting the cases, including all driver-related road traffic collisions from 2009 to 2014. Results: A total of 1842 road traffic collisions were recorded with 127 of them being driver related. There were 31 cases (24.4%) in 2014; the highest cases recorded for this study, with the least recorded in 2009 with only 12 cases (9.4%). There were 121 (95.3%) male drivers and 6 female drivers (4.7%). Most of the male drivers were between the ages of 30 and 39 with 39 cases, while that of females was between 40 and 49 years with 6 cases. There was no significant statistical correlation between age and sex ( P  = .124). No statistical correlation also existed between sex and year ( P  = .331). Pathologies of all body systems were established. Cardiovascular diseases were the most prevalent systemic medical condition seen in the drivers with 44.1%. Conclusion: The study established that the drivers had various latent medical conditions and all these could lead to possible incapacitation, affecting driver judgment, leading to collisions on the road. The National Road Safety Commission (NRSC) should request medical screening before issuing driver licenses.